Production of MAG1 Antigen of Toxoplasma gondii in Escherichia coli - Mohammad Talebzadeh; Reyhaneh Mohabati; Jalal Babaie; Samira Amiri; Mojgan Allahyari; Majid Golkar (Pasteur Institute of Iran, 2014)
Introduction : Toxoplasmosis is a parasitic infection caused by the protozoan Toxoplasma gondii it leads to serious medical problems in congenitally-infected and immunocompromised individuals, while it is quite harmless in immunocompetent individuals. Toxoplasma tissue cyst matrix protein (MAG1) induces early humoral and cell-mediated immune responses. Previous studies suggested recombinant MAG1 as a promising antigen for serodiagnosis of Toxoplasma infection. A DNA fragment encoding mag1, comprising amino acids 50 to 207, was amplified from T . gondii RH strain and cloned in prokaryotic expression plasmid pET-15b(+). The cloned DNA fragment was sequenced and showed 100% similarity with the published sequences available in GenBank Database. Recombinant MAG1 was expressed in Escherichia coli, and was highly purified in a single step by immobilized metal ion affinity chromatography. In Western blot analysis, purified protein showed a much stronger reactivity with sera from patients with acute Toxoplasma infection, compared to those with chronic infection. MAG1 protein, in combination with other acute-phase markers might be useful in discriminating acute/reactivated Toxoplasma infections from chronic forms. J Med Microbiol Infec Dis, 2014, 1 (2): 5 pages.